Matching and Structure Design Verification for Planetary Gear Two Speed Transmission - Yile Chang; Kun Yang; Jie Wang; Yu Chen; Yan Wang (Jixie chuandong)
In order to solve the problems of low average transmission efficiency of direct drive electric vehicle and the structure of traditional two shaft two speed transmission is not compact enough，a planetary gear two speed transmission scheme for electric passenger vehicles is proposed. And the parameters of power transmission system are matched，through the AVL Cruise preliminarily，the rationality for the parameter matching is verified. According to the matching result，the structural parameters for the planetary gear two speed transmission are designed. And the transmission ratio and other key parameters are modified. The three-dimensional model for the transmission is established based on CATIA. The strength for the key components is verified. Compared with the common direct scheme，the results show that the acceleration time for the whole vehicle will shorten 0.31 s when driving 100 km，the maximum climbing gradient will increase from 34% of direct drive scheme to 37%，the maximum vehicle speed will increase by 21 km/h，and the driving range under NEDC condition will also increase by 18 km. So the planetary gear type two speed transmission can effectively improve the power and economy for the whole vehicle.